The Study of Social and cultural rewards of wedding parties in Afghanistan - Dadman, Enayatullah; Mohammad Stanikzai, Sultan; Maroofi, Safiullah (Jurnal Indonesia Sosial Sains, 2023)
Marriage is a good tradition, which brings together a woman and a man Chastity, completion of honors, avoiding deviations and continuity of the generation, is important for the holy religion of Islam. In other words, marriage is a natural disaster that has become a culture after the formation of the structure of human society .The purpose of this research is to describe the social and cultural advantages of wedding parties in Afghanistan, A descriptive qualitative approach is used in this study and the data-collecting process was conducted through the techniques of interview, observation, and documentation. A marriage ceremony in Afghanistan is similar to a comprehensive collection of exhilarating observances of ancient traditions and customs. We have compiled a list of the most unique traditions of an Afghan wedding after conducting extensive research and observation.